Engineering Nanomedicine for Non-Viral RNA-Based Gene Therapy of Glioblastoma - Wenya He; Ningyang Wang; Yaping Wang; Mengyao Liu; Qian Qing; Qihang Su; Yan Zou; Yang Liu (MDPI AG, 2024)
Glioblastoma multiforme (GBM) is the most common type of malignant tumor of the central nervous system, characterized by aggressiveness, genetic instability, heterogenesis, and unpredictable clinical behavior. Disappointing results from the current clinical therapeutic methods have fueled a search for new therapeutic targets and treatment modalities. GBM is characterized by various genetic alterations, and RNA-based gene therapy has raised particular attention in GBM therapy. Here, we review the recent advances in engineered non-viral nanocarriers for RNA drug delivery to treat GBM. Therapeutic strategies concerning the brain-targeted delivery of various RNA drugs involving siRNA, microRNA, mRNA, ASO, and short-length RNA and the therapeutical mechanisms of these drugs to tackle the challenges of chemo-/radiotherapy resistance, recurrence, and incurable stem cell-like tumor cells of GBM are herein outlined. We also highlight the progress, prospects, and remaining challenges of non-viral nanocarriers-mediated RNA-based gene therapy.